Ejaculation Disorders in Male Patients with Cancer: A Systematic Review and Meta-Analysis of Prevalence. Issue 6 (21st December 2021) - Pizzol, Damiano; Trott, Mike; Grabovac, Igor; Yang, Lin; Barnett, Yvonne; Parris, Christopher; McDermott, Daragh T.; Veronese, Nicola; Kronbichler, Andreas; Ghayda, Ramy Abou; Soysal, Pinar; Jacob, Louis; et al.
Abstract : Purpose: Ejaculatory dysfunction (EjD) and erectile dysfunction after cancer treatment are clinically important complications, but their exact prevalence by various kinds of cancer site and type of treatment is unknown. The aim of this systematic review and meta-analysis was to examine the available evidence and provide pooled estimates for prevalence of EjD and erectile dysfunction in relation to all cancer sites and identify characteristics associated with EjD in cancer patients. Materials and Methods: We performed a systematic review and meta-analysis of cross-sectional and case-control studies. We searched 4 electronic databases (Medline®, CINAHL, PsychInfo and Embase®) until July 22, 2020. All retrospective or prospective studies reporting the prevalence of EjD in male patients with cancer were included in this review. A random effects meta-analysis was conducted calculating prevalence proportions with 95% confidence intervals. Prevalence proportions were calculated for the incidences of EjD by cancer site and type of treatment. Results: A total of 64 studies (a total of 10, 057 participants) were included for analysis. The most common cancer sites were bladder, colon, testis and rectum. The prevalence rates of EjD after surgical intervention ranged from 14.5% (95% CI 2.2–56.3) in colon cancer to 53.0% (95% CI 23.3–80.7) in bladder cancer. The prevalence rates of erectile dysfunction ranged from 6.8% (95% CI 0.8–39.1) in bladder cancer to 68.7% (95% CI 55.2–79.6) in cancer of the rectum. Conclusions: In a large study-level meta-analysis, we looked at a high prevalence of EjD and erectile dysfunction at various cancer sites and across different treatment types. Prospective studies of EjD and erectile dysfunction after various kinds of cancer treatments are warranted.